Determining an optimal forage-to-concentrate ratio on performance traits and blood metabolites of fattening lambs - Kashani, SMM; Gharahveysi, S; Khorshidi, KJ (Journal of the Hellenic Veterinary Medical Society, 2025)
In intensive rearing, a combination of concentrate and forage is used for lamb fattening. The research was done to determine the optimal ratio of forage-to-concentrate on male Zel fattening lambs. Twenty lambs of 16-week-old for 90 days in a completely randomized design with four treatments and five repeats were used. Treatments included forage-to-concentrate ratios (80:20, 70:30, 60:40, and 50:50). Traits were measured during the study. The collected data was analyzed by LSmeans and regression procedure in SAS software. The forage-to-concentrate ratios effect was significant on all performance traits (p<0.01). The linear change was significant in the mentioned traits(p<0.05). The effect of different forage-to-concentrate ratios was not significant on all blood metabolites (p>0.05) except cholesterol concentration (p<0.05). Based on the current findings and the limitations of increasing the concentrate consumption, the optimum ratio of forage to concentrate is suggested to be 50:50.